Deterioration of concrete mechanical properties and fracture of steel bars caused by alkali-silica reaction: A review. (January 2022) - Lu, Chunhua; Bu, Senzhuang; Zheng, Yulong; Kosa, Kenji
Highlights: About 500 data are collected to discuss the most severe decline curve of mechanical properties. The deterioration mechanism of mechanical properties caused by ASR is analyzed. A method to predict deterioration degree of practical engineering structures is promoted. Large-scale experiments are designed to discuss the fracture mechanism of steel bar. Abstract: Alkali-silica reaction (ASR) has caused many durability problems all over the world, including the deterioration of the mechanical properties of concrete and the brittle fracture of bent steel bars. The paper collects around 500 data from previous studies to sort out the varying models of deterioration for mechanical properties with ASR expansion, accompanied by discussing the deterioration mechanism and recommending application method for the actual structures, which is considered helpful for reference in the maintenance management of structures affected by ASR. Meanwhile, for the brittle fracture of steel bars, combining with the few previous research results currently available, the authors carried out in-depth discussions based on results of large-scale tests, and speculated the mechanism of the initial crack in the bent steel bar and its propagation or even the steel bar fracture under the action of concrete expansion, to further prevent the failure of steel bars and even related structures.